Uma análise sociológica dos crimes violentos patrimoniais em Cuiabá - MT - Silva, Alexandro Caetano da (2023)
This study sought to investigate the relationship between the immediate environment and the occurrence of robberies in the city of Cuiabá-MT, located in the Midwest region of the country. We started with the following research question-problem: what is the relationship between the environment and the number of robberies in Cuiabá-MT? In order to answer this question, we made the hypothetical assumption that if the environment influences the occurrence of crime, then it is possible to predict the places where crime may occur, as long as we can identify patterns in this relationship. With this in mind, the general objective of the research was to analyze the interference of the environment in the occurrence of robberies in Cuiabá-MT, between 2020 and 2021. In order to analyze these phenomena, several theories were used, among which they were distributed in six chapters that summarize the specific objectives of this research: 1) To demonstrate some characteristics of the Industrial Revolution and how this historical event shaped the formation of cities and urban spaces in general; 2) To understand that there are various forms of violence, which can take on different faces and relate them to urban spaces from macro and micro-sociological perspectives; 3) To discuss the Ecology of Crime and Environmental Criminology, exposing the situational theories of crime in the light of Environmental Criminology; 4) To expose some historical, socio-economic and urban characteristics of the city of Cuiabá; 5) To present the methodology used in the research; 6) To present and analyze the data collected in the field research. After presenting the specific objectives, we set out to present the approach used, which was quantitative, based on bibliographical and documentary research and data collection from the Observatory of the Secretaria de Estado de Segurança Pública (SESP). At the end, was carried out and the wasa descriptive data analysis statistics of robbery crimes presented using of through simple tables and graphs, referring to the Central-North and Central-South neighborhoods. Using the methodology applied, we were unable to infer whether or not there was a pattern in the crimes of robbery in the central region of Cuiabá during the period investigated, in the light of the Theories of Environmental Criminology and, therefore, it was possible to confirm the hypothesis initially launched. However, the work in question has effectively contributed to opening up new methodological perspectives in the study of urban crime in the city of Cuiabá. We hope that this research will serve as a potential starting point for new investigations in the field of environmental criminology based on the context of the victim, as well as stimulating us to think about new ways of collecting data from police reports in order to facilitate the collection of information for further analysis, both of the profile of the victims and of the criminals.